Steamship SENATOR in the ice near Nome, Alaska, n.d. - University of Washington Libraries. Special Collections Division. (1898)
On verso of image: SENATOR? Nome vicinity. In 1898, the steel passenger steamer SENATOR, was built by the Union Iron Works at San Francisco for the Pacific Coast Steamship Co. She was a single-screw vessel of 2,432 tons. She had a speed of 10.8 knots. She was taken over by the government upon her completion and carried 1,004 troops on her first voyage to Manila. Upon her return to the company she was immediately placed on the Cape Nome route from San Francisco via Seattle and Tacoma. (pp. 31-32) Notes from Gordon Newell, ed., The H.W. McCurdy Marine History of the Pacific Northwest (Seattle: Superior Publishing Co, 1966). She spent thirty years in the coastwise shipping trade between Alaska and San Diego, until she was scrapped in Osaka, Japan in 1935. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number